Evaluation of a metrology platform for an articulated arm coordinate measuring machine verification under the ASME B89.4.22-2004 and VDI 2617_9-2009 standards. (January 2017) - Acero, R.; Brau, A.; Santolaria, J.; Pueo, M.
Highlights: Revision and comparison of the applicable standards for evaluation of AACMMs. Evaluation of AACMMs new verification procedures with indexed metrology platform. AACMM's verification time reduction up to 75% with the new platform procedures. Abstract: Portable coordinate measuring instruments such as articulated arm coordinate measuring machines (AACMMs) need to be periodically evaluated according to international standards and guidelines. This work presents a revision and comparison of the applicable standards for AACMMs evaluation together with a new proposal of using of an indexed metrology platform (IMP) as an alternative method to assess the volumetric accuracy of AACMMs. Two new verification procedures using the platform are explained including an innovative methodology based on the generation of virtual reference distances. The results of the IMP verification procedures, with and without virtual distances, were compared with the evaluation procedures according to the ASME B89.4.22-2004 standard and the VDI/VDE 2617-2009 part 9 guideline, in order to assess the suitability of the proposed verification procedures with the required traceability level. The main advantages of the use of the IMP are a reduction of testing time, labor and setups, facts that will generate consequently a simplification of the AACMM's verification techniques with the derived productivity increase.